Enhancing students’ mathematical literacy ability through the implementation of the Needham learning model assisted by GeoGebra - Resy Nirawati; Fitriani Fitriani (Journal of Didactic Mathematics, 2026)
This study investigates the impact of limited learning models, conventional instructional methods, and minimal utilization of interactive technology on low mathematical literacy. It highlights a research gap in integrating the Needham model with GeoGebra for teaching linear equations. The study’s objective was to compare the mathematical literacy improvement of students taught with the Needham model supported by GeoGebra versus those receiving conventional instruction. Additionally, it aimed to assess the implementation of the Needham model assisted by GeoGebra. A quasi-experimental design with a nonequivalent pretest–posttest control group was employed. The study’s population comprised 124 eighth-grade students at State Junior High School 8 Singkawang. Purposive sampling was used to select class VIII A (25 students) as the experimental group and class VIII B (25 students) as the control group. Data analysis techniques utilized included normalized gain, t-test, and implementation percentage. The results revealed that the experimental group (N-Gain = 0.65) outperformed the control group (0.32), demonstrating a statistically significant difference (tcount = 3.243 > ttable = 2.01, p < 0.05). This indicates that students taught with the Needham model supported by GeoGebra exhibited greater improvement in mathematical literacy compared to those taught with conventional methods. The implementation of the Needham model assisted by GeoGebra was categorized as very good, exceeding the 90% threshold. Specifically, 92.37% of students achieved the desired level in the first session and 96.85% in the second session. The study concludes that the Needham model assisted by GeoGebra significantly enhances students’ mathematical literacy in learning systems of linear equations in two variables.